2017
DOI: 10.1016/j.jneuroim.2017.10.017
|View full text |Cite
|
Sign up to set email alerts
|

A role for B cells in facilitating defense against an NK cell-sensitive lung metastatic tumor is revealed by stress

Abstract: Stressors impair immune defenses and pose risks among cancer patients. Natural Killer cells are not the sole immune defense against tumor development. Utilizing an NK-sensitive tumor model, this study evaluated immune effects to stress and determined whether lung metastasis resulted from B cells’ inability to augment tumorlytic function. Lung metastasis directly correlated with delayed lung B cell accumulation compared to NK, and T cells. Decreased interleukin-12 cytokine and CD80+ molecule expression by B cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…A higher TB score was associated with a better prognosis [19]. High infiltration of B cells was closely associated with a better prognosis in a variety of tumor types, including breast, ovarian, renal cell, thyroid papillary and lung cancers [20][21][22][23]. Furthermore, TIL-Bs were related to negative lymphatic invasion in gastric cancer, lymph node metastases in papillary thyroid carcinoma, and negative distant metastasis in colorectal cancer [23,24].…”
Section: Association Between B Cells and Prognosis Of Tumor Metastasismentioning
confidence: 98%
See 1 more Smart Citation
“…A higher TB score was associated with a better prognosis [19]. High infiltration of B cells was closely associated with a better prognosis in a variety of tumor types, including breast, ovarian, renal cell, thyroid papillary and lung cancers [20][21][22][23]. Furthermore, TIL-Bs were related to negative lymphatic invasion in gastric cancer, lymph node metastases in papillary thyroid carcinoma, and negative distant metastasis in colorectal cancer [23,24].…”
Section: Association Between B Cells and Prognosis Of Tumor Metastasismentioning
confidence: 98%
“…B cells activate natural killer (NK) cells by secreting IL-12. Studies on NK-sensitive metastatic lung cancer found that when lymphocyte infiltration at the lung metastasis site was reduced by a stress test, the reduction in B cells was particularly obvious, and the secretion of IL-12 by B cells was reduced, which weakened the activation and function of NK cells and then led to an increase in lung metastasis [21]. After neutralizing B cells with antibodies, tumor metastasis increased, and the effect was similar to that of neutralizing NK cells [42,43].…”
Section: B Cells Assist Other Immune Cells In Suppressing Tumor Metas...mentioning
confidence: 99%
“…Breg-associated secretion of IgG4 promotes tumor growth [160,161] Granzyme B-expressing B cells in the microenvironment of various gynecological tumor diseases support immune tolerance to tumor antigens [24] Infiltration of tumors by Bregs as a negative predictor in breast, gastric, esophageal and squamous cell carcinomas in the head and neck region [31,[162][163][164][165] CD19 + CD24 + CD38 + Bregs as a negative prognostic factor in acute myeloid leukemia (AML) [166] Increased IL-10 production by CD19 + CD24 ++ CD27 + B cells in gastric carcinoma [31] STING-induced IL-35 + Bregs suppress NK cells in pancreas carcinoma [167] Increased number of CD19 + IL-10 + Bregs after surgery in patients with hepatocellular carcinoma (HCC) [168] Positive correlation between numbers of Bregs, regulatory T cells and TH17 cells as well as concentration of IL-10, IL-35 and BAFF in patients with primary hepatocellular carcinoma (PHC) [169,170]…”
Section: Observations With Regard To Regulatory B Cells Referencesmentioning
confidence: 99%